THE ROLE OF PSYCHOLOGICAL THERAPIES IN IMPROVING SENSORY PROCESSING ABILITIES IN CHILDREN WITH AUTISM - Khushboo; Mahdi, Anjum (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This study looked into the effectiveness of different psychological therapies in enhancing sensory processing skills among children with autism spectrum disorder (ASD). A quasi-experimental design was used to test the effects of Cognitive Behavioral Therapy (CBT), Play Therapy, Mindfulness-Based Interventions (MBIs), and Parent-Mediated Therapies in addressing sensory processing difficulties in a sample of 200 children aged 5–12 years. Sensory processing, anxiety, adaptive functioning, and parental satisfaction were assessed before and after the therapy. The results showed that 35% of participants had significant improvements in sensory processing abilities, whereas 30% of them showed moderate improvement in sensory processing ability. Play therapy has a positive effect on the integration of sensory elements in 42.5% of participants, though mindfulness interventions mainly reduce the sensory distress in 45% and improve emotional regulation in 35%. Parent-mediated therapies were more effective in enhancing daily functioning at 47.5% and creating sensory-friendly environments at 37.5%. Moreover, the most common features of sensory processing challenges included hyper-responsiveness at 55%, followed by hypo-responsiveness at 30%, and sensory-seeking behaviors at 15%. Such findings indicate that psychological therapies may be helpful in the management of children with ASD, but specific approaches may need to be taken for the diverse sensory processing profiles within this population.